Integrated Approach to the Management of Internal and External Crisis Communications in Organizations. Part 1 - T. I. Alifanova (Управленческие науки, 2019)
In spite of the fact the important place is allocated for issues of studying of crisis management situations in the field of management research and development of the organization, results of researches nevertheless remain rather fragmented which complicates the choice of the correct way in further promotion. For the solution of this task it is offered to consider the integrated structure of crises and its management based on the researches in the field of strategic management, the organizational theory and behavior as well as researches in the field of public relations and corporate communications. There are two main directions in the publications devoted to crises and its management. The first one is focused on the internal dynamics of crisis development. The second one, when the company focuses on an external stakeholder management. At first, there will be entered the basic concepts for each of the above mentioned directions in the paper, and after both directions will be united into the single integrated structure, then their common features will be highlighted and based on the researches results are offered in the extensive list of publications below. Here in the list the author assumes J. Bundy, M. Pfarrer, K. Short and T. Koombs’s research as a basis “Crisis and crisis management. Integration, interpretation and research” [1] and the article of K. Pearson and J. Klar, “Refreyming management crisis” [2]. In general, the sources list of the paper covers foreign authors works’ that had been published in 1998–2015.